Strategi Guru dalam Menanamkan Sikap Saling Menghargai Peserta Didik di Sekolah Dasar - Putri, Gisella Amelia; Lia, Inayah Kesi; Akrima, Nessa Mezhila; Dinata, Serica Aulia (Lembaga Yasin AlSys, 2023)
This article discusses the strategies used by teachers in instilling mutual respect in elementary school students. Mutual respect is a fundamental value that needs to be instilled from an early age in order to create a harmonious and inclusive learning environment. This research identified several effective strategies that teachers can use to develop mutual respect in the classroom.This research is based on qualitative research methods involving classroom observations, teacher interviews, and content analysis of relevant learning materials. The results of the study show that teachers play a key role in building mutual respect through various strategies.